Investigation of properties of epoxy coating on X80 steelunder cathodic polarization conditions - Lyudmila Nyrkova (Zaštita Materijala)
The effect of cathodic polarization on the properties of the protective epoxy coating on X80 steel samples under cyclic changes in temperature from 20 to 75 оC over a period ~3.5 months was investigated. It is shown that in a 3% NaCl solution, with decreasing polarization potential from -1.05 to -0.85 V, the disbondment radius of the epoxy coating decreased by ~3.48 times (from 10.8 to 3.1 mm). At -0.75 V and in the absence of polarization, disbondment of the coating from the steel don’t observed. By potential -0.75 V coating retains its protective properties according to the transient specific electrical resistance indicator, and its aging is slowed down.